2019
DOI: 10.1177/1073274819845874
|View full text |Cite
|
Sign up to set email alerts
|

Medicaid Expansion and Breast Cancer Screening in Appalachia and Non-Appalachia, United States, BRFSS 2003 to 2015

Abstract: Background: Prior data suggests that breast cancer screening rates are lower among women in the Appalachian region of the United States. This study examined the changes in breast cancer screening before and after the implementation of the Affordable Care Act Medicaid expansion, in Appalachia and non-Appalachia states. Methods: Data from the Behavioral Risk Factor Surveillance System between 2003 and 2015 were analyzed to evaluate changes in breast cancer screening in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…In the states that elected to participate in Medicaid expansion, women with Medicaid are similarly afforded breast cancer screening services at no cost (Kaiser Family Foundation, 2019). Despite increases in Medicaid enrollment in states that expanded Medicaid, Behavioral Risk Factor Surveillance System data reveal small or not significant increase in rates of breast cancer screening for low-income women ages 40 to 64 in these states compared with nonexpansion states (Alharbi et al., 2019; Hendryx, 2018; Valvi et al., 2019). Furthermore, the ACA established the Prevention and Public Health Fund to support statewide, territorial, and tribal health programs to improve breast cancer detection, outreach, and education (U.S.…”
mentioning
confidence: 91%
“…In the states that elected to participate in Medicaid expansion, women with Medicaid are similarly afforded breast cancer screening services at no cost (Kaiser Family Foundation, 2019). Despite increases in Medicaid enrollment in states that expanded Medicaid, Behavioral Risk Factor Surveillance System data reveal small or not significant increase in rates of breast cancer screening for low-income women ages 40 to 64 in these states compared with nonexpansion states (Alharbi et al., 2019; Hendryx, 2018; Valvi et al., 2019). Furthermore, the ACA established the Prevention and Public Health Fund to support statewide, territorial, and tribal health programs to improve breast cancer detection, outreach, and education (U.S.…”
mentioning
confidence: 91%
“…A Behavioral Risk Factor Surveillance System (BRFSS) study of women aged 50–74 years found significantly lower breast cancer screening rates in non-expansion than expansion states for non-Appalachian states (2011 to 2015) (RR = 0.95, 95% CI: 0.95–0.96) [ 40 ]. Likewise, white and Latina women displayed higher screening rates in non-Appalachian expansion than non-expansion states (rate differences of at least 3.4%), though differences were minimal for African Americans in non-Appalachian states and all groups in Appalachian states.…”
Section: Resultsmentioning
confidence: 99%
“…Uninsurance or underinsurance is associated with other social determinants of health such as belonging to a minority racial group, having a lower educational status, or earning a lower wage [ 18 , 19 ]. These characteristics predispose patients to a decreased potential of upward social mobility, influencing their overall socioeconomic status and directly obstructing access to preventive care or appropriate screening for their high risk status.…”
Section: Discussionmentioning
confidence: 99%
“…These characteristics predispose patients to a decreased potential of upward social mobility, influencing their overall socioeconomic status and directly obstructing access to preventive care or appropriate screening for their high risk status. Although non-Medicaid expansion states like Alabama did not receive additional funding to expand women’s preventive services, many non-Medicaid expansion states still experienced an increase in insurance utilization following Medicaid-expansion, likely due to the increased awareness of insurance accessibility and importance of preventive healthcare initiatives popularized by the ACA [ 18 ]. In light of the central drive for Medicaid-expansion, if Alabama were to expand Medicaid, its citizens could experience increased insurance access and access to breast cancer screening modalities, incur lower incidences of late-stage breast cancer diagnoses, and become a more health-informed population [ 20 ].…”
Section: Discussionmentioning
confidence: 99%